Biologics for generalized pustular psoriasis: a systematic review and single-arm meta-analysis - Chen, Bai-lin; Liu, Qian-wei; Dong, Xiao-wan; Bai, Yan-ping (Frontiers in Immunology, 2024)
Introduction: Generalized pustular psoriasis (GPP) is a rare and potentially life-threatening auto-inflammatory disease. Currently, there are no consensus-based guidelines or universally accepted treatments. Biologics represent a potential therapeutic option. This study systematically assessed the efficacy and safety of biologics in GPP. Methods: Relevant studies from three databases were systematically searched until June 28, 2024. Statistical information, including the single-arm proportion rate of the outcomes and 95% confidence intervals (CIs), was analyzed to determine treatment effects. Heterogeneity was assessed using I² values, and subgroup analyses were performed based on drug targets and treatment durations. Data were quantitatively synthesized using a random-effects meta-analysis. Analyses were performed using R statistical software version 4.4.0. Results: A total of 329 patients from 16 studies were included. The proportion of responders treated with IL-36 inhibitors and IL-17 inhibitors is higher than those treated with TNF-α inhibitors and IL-23 inhibitors. IL-36 inhibitors appear to achieve the highest response rates between 4 and 8 weeks, while IL-17 inhibitors, TNF-alpha inhibitors, and IL-23 inhibitors show a gradual increase in response rates up to 12 weeks. IL-36 inhibitors achieve a 40% (95% CI: 27%-54%) GPPASI75 response rate and a 55% (95% CI: 41%-68%) GPPGA (0,1) response rate within 2 weeks, significantly outperforming other biologics. The recurrence rates of GPP within 52 weeks, ranked from highest to lowest, are: IL-36 inhibitors (21% [95% CI: 9%-28%]), TNF-alpha inhibitors (20% [95% CI: 2%-46%]), IL-17 inhibitors (15% [95% CI: 1%-37%]), and IL-23 inhibitors (5% [95% CI: 0%-29%]). Additionally, 6% (95% CI: 1%-11%) of patients experienced severe adverse events. Discussion: This meta-analysis highlights the efficacy and safety of biologics in patients with GPP, offering valuable evidence to guide future clinical practice. IL-36 inhibitors show a faster and more substantial clinical response in GPP compared to other biologics. Further research is necessary to assess their role in specific subpopulations and to evaluate their potential long-term effects on flare prevention.